Mathematical model of gas hydrate of hydrogen sulfide formation during its injection into a natural layer - Khasanov M.K.; Rafikova G.R. (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования «Южно-Уральский государственный университет (национальный исследовательский университет)», 2018)
The mathematical model of liquid hydrogen sulfide injection into the semi-infinite porous layer saturated with the oil and water accompanied by H2S gas hydrate formation is presented here. We considered the case when the hydrate formation occurs at the frontal border and the oil displacement's front by hydrogen sulfide is ahead of this boundary. Solutions for pressure and temperature in every layer's area are built by help of the self-similar variable formation method. The values of the parameters of the moving interphase boundaries are found as the result of the iteration procedure. The coordinate dependence of phase boundaries on the injection pressure was studied on the basis of the obtained solutions. We have established that for the existence of solution with two different interphase boundaries, the injection pressure must be above a certain limiting value. The dependence of the limiting value of pressure on the initial temperature of the layer at different temperatures of the injected hydrogen sulphide is constructed. The results of the calculations showed that the constructed mathematical model with three areas in the reservoir gives an adequate description of the process at high injection pressures, the temperature of the injected hydrogen sulfide and the initial temperature of the layer.
Keywords: МАТЕМАТИЧЕСКАЯ МОДЕЛЬ; MATHEMATICAL MODEL; АВТОМОДЕЛЬНОЕ РЕШЕНИЕ; SELF-SIMILAR VARIABLE SOLUTION; ПОРИСТАЯ СРЕДА; POROUS MEDIUM; ФИЛЬТРАЦИЯ; FILTRATION; ГАЗОГИДРАТЫ; GAS HYDRATES; СЕРОВОДОРОД; HYDROGEN SULFIDE; 519.6+532.546